The Ideal Delegation: How Institutional Privilege Silences "Developing" Nations in the UN Climate Negotiations. (20th August 2021) - Falzon, Danielle
Abstract: In the UN climate negotiations, national delegations cannot contribute equally. Scholars have shown that "developed" countries exert greater influence than "developing" nations. This study examines how these inequalities between delegations materialize under the United Nations Framework Convention on Climate Change (UNFCCC). Drawing on 30 interviews and over 200 hours of observation at five UNFCCC meetings, I ask (1) how are institutional structures in the UNFCCC aligned with normative ideals of national development; (2) how do these ideals impact the experiences of national delegations and their negotiators; and (3) what does this reveal about institutional inequality and privilege in this context? Building on institutional and organizational studies of work and literature on Developmental Ideals, I identify four characteristics of an ideal delegation to the UNFCCC that are based in norms of national development and privileged by the structures of the institution: they are large, English-speaking, equipped with Western scientific and legal expertise, and have the ability to send the same negotiators year after year. I demonstrate how non-normative countries that cannot send an ideal delegation find that the institutional structures prohibit them from engaging effectively. Ultimately, they must develop coping mechanisms to creatively compensate for their systemic disadvantages.